2006
DOI: 10.1152/ajplung.00365.2005
|View full text |Cite
|
Sign up to set email alerts
|

Various adhesion molecules impair microvascular leukocyte kinetics in ventilator-induced lung injury

Abstract: -Although the endothelial expression of various adhesion molecules substantially differs between pulmonary microvessels, their importance for neutrophil and lymphocyte sequestration in ventilator-induced lung injury (VILI) has not been systematically analyzed. We investigated the kinetics of polymorphonuclear cells (PMN) and mononuclear cells (MN) in the acinar microcirculation of the isolated rat lung with VILI by real-time confocal laser fluorescence microscopy, with or without inhibition of ICAM-1, VCAM-1, … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
26
1

Year Published

2008
2008
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 34 publications
(27 citation statements)
references
References 36 publications
(32 reference statements)
0
26
1
Order By: Relevance
“…Furthermore, selective inhibition of tyrosine phosphorylation of ICAM-1 abolished mechanical stretch-induced PMN infiltration into the lung. Increased ICAM-1 protein expression has been shown to play a major role in the recruitment of PMNs in lungs during long-term mechanical ventilation (23,28). In the present study, however, we observed no alteration in ICAM-1 protein expression fol- Fig.…”
Section: Discussioncontrasting
confidence: 58%
“…Furthermore, selective inhibition of tyrosine phosphorylation of ICAM-1 abolished mechanical stretch-induced PMN infiltration into the lung. Increased ICAM-1 protein expression has been shown to play a major role in the recruitment of PMNs in lungs during long-term mechanical ventilation (23,28). In the present study, however, we observed no alteration in ICAM-1 protein expression fol- Fig.…”
Section: Discussioncontrasting
confidence: 58%
“…Accordingly, the histopathological tissue analysis showed considerable lung injury in the animals receiving high-volume ventilation. Moreover, cell and protein analysis of BALF showed a clear pattern of VILI in the animals subjected to overstretch: 1) increased number of neutrophils, caused by augmented endothelial and epithelial permeability [1,18]; 2) reduced counts of alveolar macrophages, consistent with the rapid decline in BALF macrophages found in other works in response to high-volume ventilation [19] and attributed to their fast inflammatory activation [20]; 3) increased total protein concentration, a hallmark of leakage in the lung barrier [1,17] having an important role in neutrophil and lymphocyte sequestration in VILI [23]. Taken together, these common biomarkers of lung injury indicate that the animals subjected to high-volume ventilation and not treated with MSCs developed VILI.…”
Section: Discussionmentioning
confidence: 56%
“…These observations suggest that the endothelial response to stretch stress may contribute to vascular inflammation. Consistent with this notion, excessive ventilatory strain on the lung quickly enhances the expression of intercellular adhesion molecule-1, vascular cell adhesion molecule-1 and P-selectin [13], which are essential adhesion molecules in mediating leukocyte recruitment during inflammation. Similarly, the inflammatory endothelial responses to mechanical stretch have also been reported in intra-arterial stent implantation, in which the local vascular wall is subjected to mechanical stretch [14,15] and in grafted veins that are stretched by high arterial pressures [16].…”
Section: Introductionmentioning
confidence: 66%